Assessment of the dynamic growth and potassium solubilization capability of three novel bacteria - IMAM HARTONO BANGUN; BUNGA RAYA KETAREN; ASRITANARNI MUNAR; PERDINANTA SEMBIRING; NURHAJIJAH NURHAJIJAH; ANDRI ABDI; REYZA SUWANTO SITORUS (Biodiversitas Journal of Biological Diversity, 2024)
Abstract. Bangun IH, Ketaren BR, Munar A, Sembiring P, Nurhajijah, Abdi A, Sitorus RS. 2024. Assessment of the dynamic growth and potassium solubilization capability of three novel bacteria. Biodiversitas 25: 177-185. Clay minerals are essential components that play a crucial role in soil cation exchangeable capacity and optimal plant growth. These components, including potassium (K), have the ability to bind with mineral crystals in the soil. Several studies have shown that K-solubilizing bacteria can facilitate the solubility of potassium, leading to optimal availability. However, the use of bacteria as biofertilizers is still limited due to challenges related to survival and growth patterns. To address these challenges, it is important to monitor the growth of the microbes and enhance their selection process to achieve effective utilization. Therefore, this study aimed to determine the bacterial growth dynamics and potential of Burkholderia paludis IHB_01, Burkholderia cepacia IHB_02, and Paraburkholderia phymatum IHB_03 in enhancing soil cation availability on clay minerals. The results showed a common initial adaptation phase among the 3 bacterial strains, followed by distinct exponential growth patterns. Burkholderia cepacia IHB_02 had the longest exponential growth phase, showing efficient resource utilization and extended growth. The results of soil cation enhancement by these bacteria showed that there were no major changes in measured parameters, such as total K, CEC, pH, and organic carbon. Furthermore, the variation in K exchange, organic carbon, and Na exchange provided insights into their unique interactions in the soil. The non-significant impact on potassium-related parameters in this study could be attributed to the presence of antagonistic cation interactions.